The social contexts of youth settings for influencing physical activity - Schlechter, Chelsey R. (Kansas State University, 2018)
Despite health benefits of physical activity (PA) in youth, worldwide estimates indicate that only 10% of children meet recommended PA guidelines of 60 minutes of moderate-to-vigorous physical activity (MVPA) per day.¹,² The places where children go to live, learn, and play influence the amount of PA children accrue,³,⁴ therefore, purpose of this dissertation was to examine social contexts of youth settings and describe contextual influences on youth PA. Chapters one and two address the methods of direct observation (DO) used to characterize contextual influences on youth PA. Chapter 1 serves as a review of the methods of current DO systems, and Chapter 2 describes the implications of using different methods to characterize contexts and PA in youth settings. Using youth sport (YS) as an example, we examined the distinct types of data that resulted from two DO systems, and discussed implications for describing influences of children’s PA. Little is known about the distribution of PA among children within setting time, such as whether social contexts promote inequalities in PA where some children are very active and others are inactive. Therefore, the purpose of the study in Chapter 3 was to describe the distribution of PA during time segmented YS practices and identify whether inequalities in PA exist. We hypothesized that inequality would vary between time segments of different contexts, specifically, that segments that fostered inclusion (i.e., optimal demand) would have lower inequality than segments that fostered exclusion (i.e., disadvantaged demand). We found that inequality in PA was varied between segment types and that social contexts of task (i.e., purpose of the segment time) and demand influenced inequality in PA. To create improvements in child population PA, we propose researchers and practitioners should focus not only on the mean PA of setting time, but also on the distribution of PA within setting time. Chapter 4 focuses on the social structure of relationships within a school district that may influence implementation of wellness policies within school systems. The study described a method and investigated the social structure between school district wellness committees and their associated elementary schools. Results of the study showed variability in the pattern of social structure between and within school districts, with some districts having a social structure with representation of schools on the district wellness committee, and other districts with no representation. As social structure characteristics influence the implementation of policies and practices within social systems, these characteristics should be investigated by researchers, and should be used to enhance implementation, rather than be disregarded. In conclusion, this dissertation provided recommendations for describing the social contexts of youth settings, provided preliminary evidence that social contexts influence the amount and distribution of PA within youth settings, and that social contexts are highly variable within and between settings. Further research is needed to find the combination of social contexts most conducive to youth PA, and future researchers should consider social contexts when designing and implementing interventions for improving youth PA within settings.
Keywords: Physical activity; Youth; Direct observation